1983
DOI: 10.1111/j.1365-2672.1983.tb02610.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substrate shock on populations of starving aquatic bacteria

Abstract: The effect of substrate (glucose) shock on starved mixed cultures of aquatic bacteria under conditions resembling the natural aquatic situation has been studied. The prevalent organism in the system was a Pseudomonas sp., and short‐term loss of viability and long‐term loss of several biochemical properties of this strain were observed. Glucose uptake rate and cell size of the population increased immediately after the shock and synchronous growth occurred subsequently. The population which became established a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Small inoculum sizes, as in our study, have even been shown to increase viable counts (13). Substrate shock caused by high substrate concentrations (42,46) has often been blamed for poor culturability. In fact, low substrate concentrations have been shown to improve cultivation success (10,13,25,43,45,56).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Small inoculum sizes, as in our study, have even been shown to increase viable counts (13). Substrate shock caused by high substrate concentrations (42,46) has often been blamed for poor culturability. In fact, low substrate concentrations have been shown to improve cultivation success (10,13,25,43,45,56).…”
Section: Discussionmentioning
confidence: 78%
“…The microorganisms remain in their habitual surroundings, and due to the diffusion from the bottom of the tube, substrate concentrations increase only slowly. This helps to avoid a substrate shock (46) but still supplies enough substrate to sustain visible growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The identification and quantification of such "r-strategists" within heterotrophic picoplankton assemblages might thus eventually allow deductions about short-term fluctuations in the availability of organic matter in aquatic habitats, e.g., for a biological monitoring of pollution effects. In contrast, many if not most of the typical free-living marine and freshwater bacteria appear to lack the ability to form colonies on solid media (282), and their growth is negatively affected by enhanced substrate levels (289).…”
Section: Patchiness and Gradientsmentioning
confidence: 99%
“…This was seen with each continuous culture assessed by colony counts on agar media. Changes in strain characteristics leading to reduced colony size, or even complete loss of ability to grow, following transfer from continuous culture to media with relatively high substrate concentrations have been observed by others (Postgate & Hunter, 1964;StraSkbova, 1983 ;Hofle, 1983), but the physiological mechanisms underlying these observations have not been elucidated. At no time did the reduction in colony size make it difficult to distinguish between colonies of strains B6/2 and DT26 on media YMGA and GA after 4 d .…”
Section: 05mentioning
confidence: 99%